Strategi Orientasi Pada Industri Manufaktur - Yeny Novita Fitriani; Joanne Andre Toy Penga; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
A strategy that focuses on the manufacturing industry is a route taken by businesses to realize long-term goals through developing habits and routines based on performance. Manufacturing or processing industries contribute more than 31 percent to the East Java economy. The strategic orientation of Surabaya city manufacturing companies includes customer care, competitor orientation, coordination between functions, and technology orientation. In 2016, the Indonesian manufacturing sector experienced an upward trend, which shows that manufacturing industry players are optimistic about facing future economic conditions. The manufacturing industry in Indonesia is an important industry for economic development because it has There is quite a large potential to increase the workforce, provide an increase in the value of raw materials, as well as increase sources of foreign exchange.